"No Trifling Matter": A Kitchen-Table Talk on Abolition and Fugitivity. Issue 2 (3rd April 2021) - McNeill, Olivia; Love, Bettina L.; Patel, Leigh; Stovall, David Omotoso
ABSTRACT: Operating within the Black radical tradition, through this kitchen-table talk, we seek to edify and sustain abolitionist ontologies. We begin with poetic and musical offerings that highlight our personal connections to abolition, before exploring the complexities and necessities of relationship building as foundational for this work. We encounter the incommensurability of doing abolitionist work within institutions and systems that have attempted, yet ultimately failed, to extinguish the light of our survival. We explore the deeply creative work of fugitivity and marronage, while re-membering the irresistible mundanity of freedom. With this autotheoretical conversation, we situate our onto-epistemological orientations within an abolitionist politic of wellness and care.